Detection of epileptic seizure using Support Vector Machine Classifier - extracted features from EEG signals - Amiz, Asef Hassan; Talukder, Md. Golam Muid; Shahriar, Labib; Chowdhury, Sahal Ahamad; Hasan, Md. Mehedi (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.